Smart Content Learning Based on Case Methods - Haryadi, Haryadi; Herliani, Rini; Sitompu, Haryani Pratiwi (International Conference on Sciences Development and Technology, 2022)
Intelligent content refers to various digital learning materials developed by Artificial Intelligence with various types of applications. Smart content implies different types of virtual content, which includes digital guides from textbooks, images, graphics, audio, video, spreadsheets, and interactive. The motive of this studies is to create an utility of highbrow studying content material primarily based totally at the case method. This research is development research (R&D) according to the ADDIE model (analysis, design, development, implementation, evaluation). The subjects of this study were students of the Accounting Education Course of the Business Feasibility Course. Product validity is shown from the results of expert validation by achieving very valid criteria for learning content application media. The practicality of the product is measured using the response instruments of lecturers and students, and the effectiveness of the product is seen from the results of the posttest conducted during field trials. As a result, the application of intelligent learning content based on the case method was shown to be effective, practical, and effective in enhancing learning effectiveness. This proves that the application of a case method-based intelligent learning content is effectively used.